ANALISIS YURIDIS TERHADAP TINDAK PIDANA DOXING DI MEDIA SOSIAL DALAM KONTEKS PERLINDUNGAN HAK PRIVASI MENURUT UNDANG-UNDANG NOMOR 27 TAHUN 2022 TENTANG PELINDUNGAN DATA PRIBADI - Miracle Graciel Kezia Wulan, Lindri Purbowati (PT Wahana Global Education, 2025)
One aspect of cybercrime that is becoming more prevalent in the expanding digital age is the dissemination of personal information, or doxing. Doxing is the dissemination of an individual's personal information without the data owner's consent. The purpose of this study is to examine how Law Number 27 of 2022 concerning Personal Data Protection regulates doxing on social media in order to guard privacy rights. Additionally, it seeks to learn about the measures taken by Indonesian law enforcement against those who disseminate personal information on social media. The research method used in writing this scientific journal is a normative juridical method, which involves examining library materials such as theories, legal principles, books, or existing previous research journals, as well as laws, regulations, and legal doctrines pertaining to research writing. In Indonesia, the practice of doxing is regulated by several laws relating to privacy, personal data theft and computer crime, including Law No. 19 of 2016 on the Amendment to Law No. 11 of 2008 on Electronic Information and Transactions, Law of the Republic of Indonesia No. 27 of 2022 on Personal Data Protection as well as the new Criminal Code. The findings reveal that, while the PDP Law has established a solid legal foundation for personal data protection, there are still issues in terms of law enforcement and public awareness.